A simulation model to comparative analysis the effect of texture bottom shape on wear and lubrication performances for micro-groove water lubricated bearings. (8th April 2021) - Jin, Da; Xiao, Ke; Xiang, Guo; Wang, Yijia; Wang, Cheng; Jia, Hang
Abstract: The novelty of this paper is to explore the role of the texture bottom shape on the transient wear performance under mixed lubrication condition using a numerical model. In the numerical model, the transient interaction between the effects of wear and mixed lubrication are analyzed by incorporating the wear depth distribution into the equation of lubrication gap in each time step. A validating experiment is performed to demonstrate the effectiveness of the numerical model. The wear and lubrication performances of bearings with five bottom shapes, i.e., semi ellipse, rectangle, isosceles triangle, left triangle and right triangle, are evaluated comparatively. Additionally, the effects of operating time, operating conditions (linear speed and external load) and some input parameters on tribological performances at different bottom shapes are discussed. The simulation results reveal that the texture bottom shape has significant effect on transient wear performance, thereinto, the groove with left triangle bottom shape obtain optimal transient wear and lubrication performances compared with the other four bottom shapes. The frictional behaviors of water lubricated bearing's contacting surface would be improved by optimizing the texture's internal structural shape especially under severe wear operating condition.